Canon and brief narrative in Venezuela: two anthologies of stories at the end of the 20th century (Dissertare, 2019)
The objective of this article is to analyze the critical and aesthetic conceptions of the Venezuelan story in the context of the anthologies published at the end of the 20th century. Through the works "El cuento venezolano. Anthology ", by José Balza (1985) and" Twentieth Century Venezuelan Tales ", by Gabriel Jiménez Emán (1989), aimed at recognizing the selection processes of authors and works, in the context of the trajectory followed by the anthologies of the story Venezuelan in the second half of the century in question. The type of research corresponds to the documentary mode, of an analytical nature. The publications studied go back to the canon of the modernist-criollista tradition and opt for an update that includes elements of contemporaneity, without dissociating from an important antecedent represented by the anthology of the Venezuelan story by Guillermo Meneses (1955). In the analyzed works incorporates writers and works of a time closer to the said anthologies, however, there is no assessment of changes and changes in gender, which, however, it is exceeded by the quality of the texts selected in these compilations.
Keywords: venezuelan tale; anthology; literary criticism